Opioid‐involved overdose trainings delivered using remote learning modalities - Nicholas A. Giordano; Sarah Febres‐Cordero; Helen Baker; Katherine M. Pfeiffer; Lisa Marie Walsh; Andy Gish; Sydney A. Axson (Wiley, 2023)
Abstract Aim This education‐focused study examined changes in nursing students' knowledge and attitudes towards responding to opioid‐involved overdoses following participation in trainings delivered using remote learning modalities. Design This pre‐post study examined learning outcomes among 17 nursing students. Methods Participants completed the Opioid Overdose Attitude Scale and Opioid Overdose Knowledge Scale to assess attitudes and knowledge, respectively. Trainings were delivered to two separate groups, one via virtual reality immersive video and another over video conferencing. Results Attitude scores increased by an average of 12.2 points and knowledge scores increased by 1.65 points. Within the virtual reality group, attitude scores increased by an average of 10 points, while no significant changes were observed in knowledge scores. The video conferencing group improved in both attitude and knowledge scores, by an average of 16.2 points and 2.1 points, respectively. Conclusions These hypothesis generating results illustrate the utility of remote learning approaches to deliver trainings, while maintaining social distance during the ongoing COVID‐19 pandemic.